Evaluation of the Breed Composition of Pork via Population Structure Analysis in Pigs - Qing Lin; Shuqi Diao; Xinyou Chen; Jinshi Du; Jiaxuan Wu; Xinshuo Zhang; Xiaohong Liu; Jiaqi Li; Zhe Zhang (Animals)
The quality of pork meat directly influences the price and consumption. The genetic improvement of pigs has mainly focused on high productive efficiency, which has resulted in poor meat quality. Crossbreeds containing commercial and indigenous breeds could improve the meat quality, but identifying breed composition was difficult because of the lack of an ancestry reference panel. Therefore, we first constructed an abundant reference panel and convenient pipeline to identify ancestry/breed composition. The ancestry reference panel consisted of 517 reliable individuals, including three commercial breeds (Duroc, Landrace, and Yorkshire) and 38 indigenous Chinese breeds. The nature of the reference panel showed that the European domestic breed (EUD) and Asian domestic breed (ASD) were distinctly divided into two clusters. The evaluation of ancestry identification revealed that the reference panel performed well in identifying EUD and ASD ancestry proportions for commercial breeds, indigenous breeds, and crossbreeds. In addition, the ancestry reference panel also performed excellently in identifying breed composition for 3 commercial and 38 indigenous breeds. Specifically, the reference panel showed the outstanding identification of breed composition for crossbred individuals. These results suggested that the ancestry reference panel and convenient pipeline played a good role in identifying breed composition for pigs.